2012
DOI: 10.1016/j.annemergmed.2011.09.018
|View full text |Cite
|
Sign up to set email alerts
|

System-Level Health Disparities in California Emergency Departments: Minorities and Medicaid Patients Are at Higher Risk of Losing Their Emergency Departments

Abstract: Study Objective Emergency Department (ED) closures threaten community access to emergency services, but few data exist to describe factors associated with closure. We evaluated factors associated with ED closure in California and sought to determine if hospitals serving more vulnerable populations have a higher rate of ED closure. Methods Retrospective cohort study of California hospital EDs between 1998 and 2008, using hospital and patient level data from the California Office of Statewide Planning and Deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…15,16 Unlike other patient-level factors such as age and race, insurance status of patients has a direct effect on trauma centers' financial viability. 17,18 A hospital's financial standing influences its quality of care by providing the means for increased staffing levels, newer technology, and more active quality improvement programs. 19Y22 Because of this, it is plausible that hospitals with a disproportionate share of uninsured patients, that is, safety net hospitals, could have more adverse outcomes overall.…”
mentioning
confidence: 99%
“…15,16 Unlike other patient-level factors such as age and race, insurance status of patients has a direct effect on trauma centers' financial viability. 17,18 A hospital's financial standing influences its quality of care by providing the means for increased staffing levels, newer technology, and more active quality improvement programs. 19Y22 Because of this, it is plausible that hospitals with a disproportionate share of uninsured patients, that is, safety net hospitals, could have more adverse outcomes overall.…”
mentioning
confidence: 99%
“…However, these results are similar to those found in studies of other states, which demonstrate that hospital closures differentially affect vulnerable populations. [33][34][35] In addition, a comprehensive study of factors associated with ED closures in the United States has shown that EDs are more likely to close if they are characterized by for-profit ownership, location in a competitive market, safety net status, and low profit margin when fully adjusting for other factors. 4 This study also demonstrates that spatial analysis can be used to predict changes in ED volume related to hospital closures.…”
Section: Discussionmentioning
confidence: 99%
“…Several environmental factors, including residential location, hazards and pollutants, have been implicated in racial and ethnic health disparities in hypertension [9,24,25]. For example, older Chinese Americans who live in urban areas have more healthcare resources than those who live in rural areas [19].…”
Section: Environmental Factorsmentioning
confidence: 99%